Human Resource Cost Management: Balancing Employee Welfare and Corporate Profitability - Suwaji, Rifki (Journal of Economic Education and Entrepreneurship Studies, 2024)
Human resource cost management is a crucial aspect of corporate business strategy to ensure a balance between employee welfare and profitability. This study aims to analyze the impact of human resource cost management on employee welfare and its effect on corporate profitability, using GoTo Group as a case study. A quantitative approach is applied with a linear regression analysis method to examine the relationship between the independent variable (human resource cost management), the mediating variable (employee welfare), and the dependent variable (corporate profitability). Data were collected through employee surveys at GoTo and an analysis of financial reports and HR policies. The results show that human resource cost management significantly affects employee welfare (β = 0.45, p-value = 0.000), while employee welfare positively contributes to corporate profitability (β = 0.30, p-value = 0.001). These findings suggest that cost efficiency strategies that consider employee welfare can enhance productivity and corporate competitiveness. Additionally, work flexibility plays a vital role in improving employee satisfaction and retention. This study recommends that technology-based companies such as GoTo Group develop data-driven strategies to optimize sustainable HR policies that positively impact long-term profitability.